Picture Sequences to Enhance Students’ Narrative Writing - Swari, Utami Ratna; Analisa, Ary; Arista, Hermin (Journal of Education Research, 2024)
The objective is to determine how picture sequences can be implemented to enhance twenty three students’ narrative writing one st-semester Informatics students in Panca Marga University Probolinggo. This research is performed in two cycles. Qualitative data are obtained from observation checklists, field notes, and questionnaires. At the same time, quantitative data are gained from the product of students’ narrative writing. The research shows that using picture sequences can improve students’ narrative writing. The scoring rubrics are Level one = Poor, two Fair, three=Good, and  four=Excellent. It is considered a success if sixty five percent of the students reach level three or more. In the preliminary study, thirty five percent of students reached level three or more. After cycle two, seventy eight percent of students reach level three or more. It indicates that picture sequences can improve students’ narrative writing.